Measurement Accuracy of Ultrasound Viscoelastic Creep Imaging in Measuring the Viscoelastic Properties of Heterogeneous Materials - Lin, Che-Yu; Chen, Yi-Cheng; Pang, Chin Pok; Yang, Tung-Han (Advances in Technology Innovation, 2022)
Ultrasound viscoelastic creep imaging (UVCI) is a newly developed technology aiming to measure the viscoelastic properties of materials. The purpose of this study is to investigate the accuracy of UVCI in measuring the viscoelastic properties of heterogeneous materials that mimic pathological lesions and normal tissues. The finite element simulation is used to investigate the measurement accuracy of UVCI on three material models, including a homogeneous material, a single-inclusion phantom, and a three-layer structure. The measurement accuracy for a viscoelastic property is determined by the difference between the simulated measurement result of that viscoelastic property and its true value defined during the simulation process. The results show that UVCI in general cannot accurately measure the true values of the viscoelastic properties of a heterogeneous material, demonstrating the need to further improve the theories and technologies relevant to UVCI to improve its measurement accuracy on tissue-like heterogeneous materials.